FRAMED: An AutoML Approach for Structural Performance Prediction of Bicycle Frames. (March 2023) - Regenwetter, Lyle; Weaver, Colin; Ahmed, Faez
Abstract: This paper demonstrates how Automated Machine Learning (AutoML) methods can be used as effective surrogate models in engineering design problems. To do so, we consider the challenging problem of structurally-performant bicycle frame design and demonstrate across-the-board dominance by AutoML in regression and classification surrogate modeling tasks. We also introduce FRAMED — a parametric dataset of 4500 bicycle frames based on bicycles designed by practitioners and enthusiasts worldwide. Accompanying these frame designs, we provide ten structural performance values such as weight, displacements under load, and safety factors computed using finite element simulations for all the bicycle frame designs. We formulate two challenging test problems: a performance-prediction regression problem and a feasibility-prediction classification problem. We then systematically search for optimal surrogate models using Bayesian hyperparameter tuning and neural architecture search. Finally, we show how a state-of-the-art AutoML method can be effective for both regression and classification problems. We demonstrate that the proposed AutoML models outperform the strongest gradient boosting and neural network surrogates identified through Bayesian optimization by an improved F1 score of 24% for classification and reduced mean absolute error by 12.5% for regression. Our work introduces a dataset for bicycle design practitioners, provides two benchmark problems for surrogate modeling researchers, and demonstrates the advantages of AutoML in machine learning tasks. The dataset and code are provided at . Graphical abstract: Highlights: A dataset of structural performance for 4500 community-designed bicycle frames. Validation of Finite Element results against physical testing of bicycle frames. Optimal surrogate models trained using Automated Machine Learning (AutoML). Validation of surrogates against baselines tuned through Bayesian optimization.